A qualitative view of the HIV epidemic in coastal Ecuador - Beckman,Adam L.; Wilson,Magdalena M.; Prabhu,Vishaal; Soekoe,Nicola; Mata,Humberto; Grau,Lauretta E. (PeerJ, 2016)
In 2013 approximately 37,000 people were living with HIV in Ecuador (prevalence 0.4%), representing a generalized epidemic where most new infections arise from sexual interactions in the general population. Studies that examine attitudes towards people living with HIV (PLWH), individual risk perception of acquiring HIV amongst Ecuadorians, and the ways in which levels of risk perception may affect risk behaviors are lacking. This qualitative study aimed to fill this gap in the literature by investigating these issues in the rural, coastal community of Manglaralto, Ecuador, which has among the highest incidence of HIV in Ecuador. We conducted interviews with 15 patients at Manglaralto Hospital. Analysis of interview transcripts revealed widespread negative attitudes towards PLWH, prevalent risk behaviors such as multiple sex partners and lack of condom use, and low individual risk-perception of contracting HIV. These findings underscore the need for increased efforts to prevent further growth of the HIV epidemic in Ecuador.
Keywords: HIV/AIDS; HIV risk perception; HIV risk behavior; HIV attitudes; Ecuador; Global health; Public health; Latin America; Risk behavior; Qualitative